2022
DOI: 10.3390/cells11020225
|View full text |Cite
|
Sign up to set email alerts
|

Sapienic Acid Metabolism Influences Membrane Plasticity and Protein Signaling in Breast Cancer Cell Lines

Abstract: The importance of sapienic acid (6c-16:1), a monounsaturated fatty acid of the n-10 family formed from palmitic acid by delta-6 desaturase, and of its metabolism to 8c-18:1 and sebaleic acid (5c,8c-18:2) has been recently assessed in cancer. Data are lacking on the association between signaling cascades and exposure to sapienic acid comparing cell lines of the same cancer type. We used 50 μM sapienic acid supplementation, a non-toxic concentration, to cultivate MCF-7 and 2 triple-negative breast cancer cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
0
7
0
2
Order By: Relevance
“…Instead of relying on the canonical SCD pathway for fatty-acid desaturation, tumor cells appear to exploit a different enzyme, FADS2, and upregulate this alternative route when SCD is inhibited [ 22 ]. 16:1n-10, generated by this route, has received attention as a novel marker of cancer cell plasticity owing to the elevated levels of this fatty acid in several cancer cell lines, mouse hepatocellular carcinoma, and primary human liver and lung carcinomas [ 22 , 129 , 130 ]. Thus, 16:1n-10 biosynthesis through FADS2 constitutes an alternative source of MUFA to support the proliferation of the tumor cells, which may involve, among other actions, increasing membrane fluidity [ 11 , 129 ].…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of relying on the canonical SCD pathway for fatty-acid desaturation, tumor cells appear to exploit a different enzyme, FADS2, and upregulate this alternative route when SCD is inhibited [ 22 ]. 16:1n-10, generated by this route, has received attention as a novel marker of cancer cell plasticity owing to the elevated levels of this fatty acid in several cancer cell lines, mouse hepatocellular carcinoma, and primary human liver and lung carcinomas [ 22 , 129 , 130 ]. Thus, 16:1n-10 biosynthesis through FADS2 constitutes an alternative source of MUFA to support the proliferation of the tumor cells, which may involve, among other actions, increasing membrane fluidity [ 11 , 129 ].…”
Section: Cancermentioning
confidence: 99%
“…Thus, 16:1n-10 biosynthesis through FADS2 constitutes an alternative source of MUFA to support the proliferation of the tumor cells, which may involve, among other actions, increasing membrane fluidity [ 11 , 129 ]. In addition, 16:1n-10 may also affect the EGFR/AKT/mTOR cascade, which is a critical pathway in tumors to support growth, survival, and metastasis [ 130 ]. 16:1n-10, however, may not interfere with the mitogen-activated protein kinase signaling cascade [ 10 ].…”
Section: Cancermentioning
confidence: 99%
“…In these cases, it would help to keep in mind the alternative delta-6 desaturase pathway giving relevance to the follow-up of sapienic acid metabolism. More recently, in cancer cells, it was shown that sapienic acid supplementation induces changes in growth factors and proliferative signaling [ 60 ].…”
Section: The Role Of Lipogenesis and Ketogenic Diets In Cancermentioning
confidence: 99%
“…El ácido sapiénico, como ya se ha mencionado, es un componente mayoritario del sebo humano, donde se ha estudiado su acción antibacteriana frente a bacterias Gram-positivas (229,230). Por otra parte, el ácido sapiénico ha llamado la atención como un nuevo marcador de la plasticidad de las células cancerosas (200,(231)(232)(233). Un estudio reciente, ha identificado la biosíntesis de ácido sapiénico como una fuente alternativa de ácidos grasos monoinsaturados en diferentes líneas celulares de cáncer de ratón y humano (231).…”
Section: Inmunesunclassified
“…El enriquecimiento de células Caco-2 (modelo de cáncer de colon humano) con ácido sapiénico da lugar a un aumento de la fluidez de la membrana y de la supervivencia celular y a la biosíntesis por elongación y desaturación de la familia n- 10 (200,233). Además de presentar los efectos biofísicos comentados, el ácido sapiénico puede influir en la cascada EGFR/AKT/mTOR, que es una vía fundamental presente de forma ubicua en los tumores para mantener el crecimiento, la supervivencia y la metástasis (232).…”
Section: Inmunesunclassified